Peningkatan Hasil Belajar Matematika melalui Model Double Loop Problem Solving Siswa di Kelas VII-A - Maya Sumiati (STKIP Andi Matappa Pangkep, 2023)
The aim of the research was to improve student learning outcomes in class VII-a social arithmetic material at SMPN 1 Cimenyan. This research is made by improve student learning processes and outcomes in learning mathematics and applying a learning approach to build students active in their own knowledge and develop skills in solving problems. The formulation of the problem from this study is described in the form of a question, namely